PENINGKATAN KEPUTUSAN MEMBELI KARTU PRABAYAR INDOSAT DI KECAMATAN MOJOGEDANG MELALUI KUALITAS PRODUK, HARGA DAN PROMOSI - Linda Nur Susila; Andreyan Kyky Himawan (KELOLA, 2019)
The purpose of this study is to find out empirically the effect of product quality (X1), price (X2) and promotion (X3) on the decision to buy an Indosat prepaid card in Mojogedang District (Y). In this study data was collected through a questionnaire on 100 respondents of Indosat prepaid card buyers in Mojogedang District by using an accidental sampling technique to determine respondents' responses to each variable. Data analysis includes validity test, reliability test, classic assumption test, multiple linear analysis, t test, F test and test coefficient of determination (R2). The results of multiple linear analysis that product quality, price and promotion have a positive effect on the decision to buy a Indosat prepaid card in Mojogedang District. The results of the t test show that productquality and promotion have a significant effect, while the price has no significant effect on the decision to buy an Indosat prepaid card in Mojogedang District. From the F test, the conclusion is that there is a significant effect on the product and promotion, while the price has an influence but is not significant towards the decision to buy an Indosat prepaid card in Mojogedang District. The adjusted R Square number is 0.715 which means that the variables of product quality, price and promotion can influence the decision variable to buy 71.5%, the remaining 28.5% is influenced by other variables outside of this study. For example: brand image and location.